2012
DOI: 10.18632/oncotarget.497
|View full text |Cite
|
Sign up to set email alerts
|

On the presence and role of human gene-body DNA methylation

Abstract: ABSTRACT:DNA methylation of promoter sequences is a repressive epigenetic mark that down-regulates gene expression. However, DNA methylation is more prevalent within gene-bodies than seen for promoters, and gene-body methylation has been observed to be positively correlated with gene expression levels. This paradox remains unexplained, and accordingly the role of DNA methylation in gene-bodies is poorly understood. We addressed the presence and role of human gene-body DNA methylation using a meta-analysis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
330
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(391 citation statements)
references
References 47 publications
57
330
2
2
Order By: Relevance
“…This observation is in accord with previous studies that find consistently high methylation in mammalian gene bodies (34,35). A recent study in rice, however, found that gene-body methylation and divergence is associated with their evolutionary age (36).…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in accord with previous studies that find consistently high methylation in mammalian gene bodies (34,35). A recent study in rice, however, found that gene-body methylation and divergence is associated with their evolutionary age (36).…”
Section: Discussionsupporting
confidence: 92%
“…13 Recent literature, however, suggests that body methylation may play an equally important role in controlling gene expression. 17,18 Less than 1% of the promoter and body CpG sites represented on the BeadChip are hypermethylated in both TMX2-11 and TMX2-28 and of these dmCpGs, slightly more are in the body than in the promoter region (0.66% vs. 0.52%).…”
Section: Discussionmentioning
confidence: 99%
“…Gene-body methylation identified 'orphan promoters', which may be used in the early stages of development (30). Hypermethylation of gene-bodies frequently indicates higher levels of gene expression in human tissues and cell types (8,31). Aberrant methylation of the gene body was observed to contribute to the risk of heart failure (32) and coronary heart disease (23).…”
Section: Discussionmentioning
confidence: 99%
“…Gene-body methylation was found to be positively correlated with gene expression (8). Although the functions of the gene-body CpG island (CGI) remain to be elucidated, methylation of the gene-body is frequently associated with active transcription in humans and other animals (9).…”
Section: Introductionmentioning
confidence: 99%